Soil properties rather than plant diversity mediate the response of soil bacterial community to N and P additions in an alpine meadow - Lin, Zhenrong; Shi, Lina; Wei, Xiaoting; Han, Bing; Peng, Cuoji; Yao, Zeying; Xiao, Qing; Lu, Xinmin; Deng, Yanfang; Zhou, Huakun; Liu, Kesi; Shao, Xinqing (Frontiers in Microbiology, 2022)
The alpine meadow in Qinghai-Tibetan Plateau, which is susceptible to global climate change and human activities, is subject to nutrient addition such as nitrogen (N) and phosphorus (P) to enhance soil available nutrients and ecosystem productivity. Soil bacterial communities partly driver the effects of nutrient additions on ecosystem progress, whereas scarce research have clarified the effects of N and P addition as well as their determinant factors. We conducted a N and P additions experiment in an alpine meadow ecosystem on the Qinghai-Tibetan Plateau with four treatments: untreated control (CK), N addition (N), P addition (P), and NP addition (NP). We employed a high-throughput Illumina Miseq sequencing technology to investigate the response of soil bacterial communities to short-term N and P additions. N and P addition decreased soil bacterial richness (OTU numbers and Chao 1 index), and P addition decreased soil bacterial diversity (Shannon and Simpson indices). The results from structural equation modeling (SEM) indicated that N addition indirectly acted on soil bacterial communities through altering soil available nutrients and pH, while addition indirectly affected bacterial communities by increasing soil P availability. N addition directly induced the change of soil NH4+-N, and then affected plant diversity. Additionally, we found that the response of plant diversity to N and P additions was uncoupled with soil bacterial diversity. Short-term nutrient additions altered soil bacterial community structure in alpine meadow ecosystems and the changes were mediated by soil properties. These results indicated that short-term nutrient additions led to a reduction of soil bacterial community diversity in fragile alpine environments, thereby altered ecosystem processes.